Decision Support System for Village Head Election Using the Weighted Product Method: Case Study in Lumar Village - Noviyanti; Angelia Deli; Laura Gloria (novamindpress, 2025)
The election of the village head is an important process in determining leaders who can manage the village government effectively and meet the needs of the community. Election leader of village is very important to determine the direction of the region and the importance of the capabilities of the chosen leader based on real data. This study discusses the application of the Weighted Product (WP) method in the decision-making support system for the election of village heads in Lumar Village. The WP method is used because it is able to handle various criteria by giving weight to each criterion according to its level of importance. The criteria used include work experience, education, integrity, and community support. This system is designed to process data in a structured and transparent manner, generating a preference value for each prospective village head. The candidate with the highest score is considered the most qualified. The results of the study show that the WP method improves the accuracy, objectivity, and efficiency of the village head election process, resulting in accountable decisions.